AN INTELLIGENT CONTROL TECHNIQUES FOR MPPT IN SOLAR PHOTOVOLTAIC SYSTEM - et. al, Vidhya Fulmali Dr (International Journal of Advanced Science and Technology, 2020)
In the sector of energy conversion, solar power is the primary source of energy. The significant task is the methods to produce peak energy from easy PV modules. Power electronics were instrumental in achieving the objective to a higher level. This article attempts to explore and analyse various MPPT methods used in distinct situations to render it easy to select a specific methodology for a specific scenario. The MPPT is responsible for extracting from the photovoltaic as much power as possible and feeding it to the load steps up to the required magnitude. The main goal would be to monitor the photovoltaic module's peak powerpoint to obtain the maximum possible power from the photovoltaic. This study operates to explore in-depth the notion of the Advance Convolution cellular network (ACNN) model under temporary shading situation which considerably improves the solar photovoltaic system's effectiveness. Development of device modelling design consisting primarily of renewable PV, converter together with P&O, Inc, CVC and new profound learning techniques (Advance CNN techniques). The findings achieved indicate adequate efficiency in aspects of stabilization, precision and moment reaction under varying circumstances. To provide a simple contrast, standard and novel algorithms are described using flowcharts and analytical information.